1996
DOI: 10.1002/clc.4960190706
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and fibrinolytic parameters in patients with pulmonary hypertension

Abstract: SummaryB~~ckground: Vascular endothelium reacts to various pathophysiologic stimuli by releasing several autocoids and cytokines that can be used along with the coagulation and fibrinolytic markers for the diagnosis of hemostatic alterations. Several newer markers for vascular distress. such as tissue plasminogen activator (TPA), tissue plasminogen activator inhibitor-I (PAI-1 ), TPMAI-1 complex, and the newly reported inhibitor of the coagulation process, namely, tissue factor pathway inhibitor (TFPI), have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 23 publications
0
29
2
2
Order By: Relevance
“…Increased antigenic concentration has been reported (8), while baseline activity of PAI-1 has been shown to be normal in these patients (7,8). In spite of previous observation of hypoxia-induced transcription of the PAI-1 gene in vascular endothelial cells (28), we failed to demonstrate any significant differences in baseline PAI-1 between the study groups and controls.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Increased antigenic concentration has been reported (8), while baseline activity of PAI-1 has been shown to be normal in these patients (7,8). In spite of previous observation of hypoxia-induced transcription of the PAI-1 gene in vascular endothelial cells (28), we failed to demonstrate any significant differences in baseline PAI-1 between the study groups and controls.…”
Section: Discussioncontrasting
confidence: 73%
“…Although previous studies have demonstrated abnormal endothelial function and altered coagulation and fibrinolysis in patients with pulmonary hypertension (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), there are few reports focusing on endothelial dysfunction and intravascular coagulation in the particular setting of the Eisenmenger syndrome. Decreased plasma thrombomodulin has been observed in these patients, suggestive of decreased availability of this anticoagulant proteoglycan on the surface of endothelial cells (5,16).…”
mentioning
confidence: 99%
“…In humans, increased pulmonary expression of TF, an increase in TF-bearing microparticles, and a decrease in circulating forms of TFPI have been noted (26,27). TF is also expressed in pulmonary plexiform-like lesions in humans and in a rat model of severe pulmonary hypertension (28,29).…”
mentioning
confidence: 99%
“…These mechanisms are mediated by 1 or more molecular and cellular processes, including the following: reduced prostacyclin availability caused by diminished endothelial cell prostacyclin synthase activity 25 ; elevated endothelin levels resulting from enhanced production and reduced pulmonary clearance [26][27][28] ; decreased nitric oxide synthase expression 29,30 ; elevated plasma levels and low platelet 5-hydoxytryptamine levels 31 ; down-regulation of voltage-gated potassium (eg, Kv1.5) channels of pulmonary vascular smooth muscle cells 32,33 ; activity of autoantibodies and proinflammatory cytokines 34,35 ; and prothrombotic states arising from endothelial, coagulation, and fibrinolytic cascade and platelet dysfunction. [36][37][38][39] These abnormalities give rise to a predisposition to vasoconstriction over vasodilation of the pulmonary vascu-FIGURE 1. The 3 mechanistic pathways known to be disturbed in patients with pulmonary arterial hypertension (PAH).…”
Section: Molecular and Cellular Mechanismsmentioning
confidence: 99%